First records of four orchid bee species (Hymenoptera, Apidae: Euglossini) in Ecuador - Alexandra D. Hernández Hernández; Marcio L. de Oliveira; David R. Diaz-Guevara; Cristina Alarcón-Ortiz; Alex Pazmiño-Palomino (Journal of Insect Biodiversity and Systematics)
Orchid bees (Hymenoptera, Apidae, Euglossini) play a vital role as key pollinators in the Neotropical forests. Their preference for forested areas makes these bees more susceptible to environmental changes, particularly in areas under severe human impact, such as the Chocó-Darien biodiversity hotspot. This study presents new data on orchid bees within the Canandé Biological Reserve, a lowland rainforest in the Chocó region of northwestern Ecuador. At this site, four species of orchid bees were recorded for the first time in Ecuador: Euglossa bursigera Moure, 1970, Euglossa crassipunctata Moure, 1968, Euglossa villosiventris Moure, 1968 and Eufriesea macroglossa (Moure, 1965). We also provide species-specific information on diagnosis, distribution maps, and high-resolution images. With these records, the total number of orchid bee species recorded in Ecuador now stands at 119.